Cotidiano e resistência da classe trabalhadora na periferia urbana de Campinas SP: expressões manifestas no Jardim Bassoli - Alves, Mônica Clavico (2015)
The main objective of the present work was to explore the everyday life through the means of resistance of a suburb s residents of a city of Campinas, in a district created by a federal government program called ―Minha Casa, Minha Vida (My House, My Life). Therefore, the theoretical background addressed the totality of questions in a direct relationship with the researched object, such as the production and reproduction social relations in the capitalism, the specific questions regarding the study s context related to the habitation question, the everyday life and the ways resistance of the works throughout the history and the studied district. We have performed a qualitative social research using the dialectical materialism method and a semi-structured script for interviews as the data collect technique. We concluded, in our study, the degradation of the life condition of the residents as a result of the contradiction of the capitalist society, where the social produced wealth is privately appropriated as well as the resistance demonstrations of the workers, followed by contemporary historical traces, mostly institutional, that reinforces the representativism, individual demonstrations of resistance, fragmentation of the organization and the possibility for militancy work that assures the class consciousness and the autonomous organization of the workers